Restructuring large housing estates in Europe - Kempen, Ronald van 1958-2016 (Policy Press, 2005)
All over Europe, post Second World War large-scale housing estates face physical, economic, social and cultural problems. This book presents the key findings of a major EU-funded research programme into the restructuring of twenty-nine large-scale housing estates in Northern, Western, Southern and Eastern Europe. Policy and practice between and within the ten countries studied - UK, the Netherlands, Sweden, Germany, Poland, Hungary, Slovenia, Italy, Spain, and France - is compared. While existing literature focuses on the negative aspects of large-scale housing estates, this book starts from the premise that the estates can be transformed into attractive places to live and focuses on the possibilities of sustainability and renewal through social, physical and policy actions. Specifically, the book: explains the origins and nature of contemporary problems on the estates; examines which policy objectives, measures and processes have had the greatest impact; assesses and compares a wide range of local, regional and national initiatives; discusses current ideas and philosophies, such as 'place making' and 'collaborative planning' that are likely to influence future policy and practice; and provides good practice guidance for neighbourhood sustainability and renewal. Written by a multi-national team of experts and drawing on original fieldwork, the book provides unique comparative insights into the present and future position of large-scale housing estates in Europe. Restructuring large housing estates in Europe is an invaluable resource for a wide audience of academics, researchers, students and policy makers in the fields of housing, urban studies, community studies, regeneration, planning and social policy. The editors are specialists in housing and urban research at the Universities of Utrecht in the Netherlands, Birmingham in the UK and the Metropolitan Research Institute in Budapest, Hungary